Anesthesiologists' airway management expertise: Identifying subjective and objective knowledge gaps. Issue 1 (21st September 2020) - Bessmann, Ebbe L.; Rasmussen, Lars S.; Konge, Lars; Kristensen, Michael S.; Rewers, Mikael; Kotinis, Alexandros; Rosenstock, Charlotte V.; Graeser, Karin; Pfeiffer, Peter; Lauritsen, Torsten; Østergaard, Doris; ,
Abstract : Background: Failure in airway management continues to cause preventable patient harm, and the recommended continuing education is challenged by anesthesiologists' unknown knowledge gaps. This study aimed to identify anesthesiologists' subjective and objective knowledge gaps as well as areas where anesthesiologists are incorrect and unaware . Methods: An adaptive E‐learning program with 103 questions on adult airway management was used for subjective and objective assessment of anesthesiologists' knowledge. All anesthesiologists in the Capital Region of Denmark were invited to participate. Results: The response rate was 67% (191/285). For preoperative planning, participants stated low confidence (subjective assessment) regarding predictors of difficult airway management in particular (69.1%‐79.1%). Test scores (objective assessment) were lowest for obstructive sleep apnea as a predictor of difficult airway management (28.8% correct), with participants being incorrect and unaware in 33.5% of the answers. For optimization of basic techniques, the lowest confidence ratings related to patient positioning and prediction of difficulties (57.4%‐83.2%), which agreed with the lowest test scores. Concerning advanced techniques, videolaryngoscopy prompted the lowest confidence (72.4%‐85.9%), while emergency cricothyrotomy resulted in the lowest test scores (47.4%‐67.8%). Subjective and objective assessments correlated and lower confidence was associated with lower test scores: preoperative planning [ r  = −.58, P  < .001], optimization of basic techniques [ r  = −.58, P  = .002], and advanced techniques [ r  = −.71, P  < .001]. Conclusion: We identified knowledge gaps in important areas of adult airway management with differing findings from the subjective and objective assessments. This underlines the importance of objective assessment to guide continuing education.